EKSISTENSI KLAUSULA PELARUNGAN BAGI SEAFARER DI INDONESIA - Sintong Arion Hutapea; Winanda Kusuma; A. Cery Kurnia (LPPM Universitas Ekasakti Padang, 2021)
In the world of shipping, seafarers are bound by a Seawork Agreement (PKL) which contains requirements that must be obeyed by the parties. This includes a clause that is included in the seafarer's employment contract. Implications arising from the burial of the seafarer's corpse. The existence of a banning clause in the seafarer's employment contract. The role of the state in providing legal protection for seafarers from confinement. The ban must meet 4 formal requirements. The unbalanced bargaining position makes entrepreneurs and seafarers as parties ban clauses can appear in street vendors. Finally, the seafarer inevitably has to obey the PKL that has been agreed with the entrepreneur. States intervenes in ensuring the protection of human rights for seafarers from the prohibition clause, it needs to be done by making changes to the legal system which includes the legal structure, legal substance and legal culture